Manajemen Unit Produksi Berbasis Inovasi Produk (Studi pada SMK Negeri 7 Purworejo) - Budi Swityastuti; Budi Sutrisno (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2014)
The purpose of this study was to obtain an overview of: planning, implementation and supervision of the production unit based product innovations developed in SMK Negeri 7Purworedjo. This research was qualitative by ethnography design. The research was was SMK 7 Purworedjo focusing on innovation sanitary napkins that can be washed and reused brand “Siklus”. Data collection was conducted in a natural setting and techniques of data collection were through participant observation, in-depth interviews and documentation. Data analysis techniques were done through four phases namely data collection, data reduction, data display and conclusion. The results of the study are (1) Planning UPJ (Unit Production/Services) consider factors: purpose, type of production, targeting, marketing, resources, sharing, managing, availability of raw materials and place of execution, (2) Implementation of UPJ includes : organizing, production, delivery and implementation prakerin students, (3) Supervision UPJ includes: the quality of the product by the management, administration by the principal, and students prakerin by tutors. This study recommends that the product innovations of UPJ SMK 7 Purworedjo are circulated out of the city product innovations of UPJ SMK 7 Purworedjo are circulated out of the city.